Clindamycin-Induced CovS-Mediated Regulation of the Production of Virulent Exoproteins Streptolysin O, NAD Glycohydrolase, and Streptokinase in Streptococcus pyogenes - Minami, Masaaki (American Society for Microbiology (ASM), 2010)
The administration of high-dose clindamycin (CLI) along with penicillin is recommended for the treatment of streptococcal toxic shock syndrome. However, the prevalence of CLI-resistant Streptococcus pyogenes strains is increasing worldwide, and the effect of CLI on CLI-resistant S. pyogenes strains remains unknown. We aimed to evaluate the effect of CLI on the in vitro production of three major virulent exoproteins, namely, streptolysin O (Slo), NAD glycohydrolase (Nga), and streptokinase (Ska), by CLI-resistant S. pyogenes strains. After the incubation of M1 serotype CLI-resistant S. pyogenes D2TY in the presence of 1 μg/ml CLI, the amounts of Slo, Nga, and Ska and the levels of slo, nga, and ska mRNA in the supernatant were analyzed by Northern blotting and Western blotting, respectively. The results of both assays showed that the production of Slo, Nga, and Ska was higher with CLI treatment than without CLI treatment. We evaluated the role of the sensor kinase CovS, which is involved in the two-component system of S. pyogenes, in the CLI-induced production of these three exoproteins. Northern blotting analysis revealed that CLI induced the expression of covS mRNA in wild-type strain D2TY. Furthermore, both Northern blotting and Western blotting analyses showed that CLI decreased the levels of expression of Slo, Nga, and Ska in isogenic covS mutant D2TYcovS. These results suggest that CLI increases the production of three virulent exoproteins in CLI-resistant S. pyogenes strains via the action of CovS.